My home was my castle: evictions and repossessions in Britain - René Böheim; Mark P. Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2000)
Using data for 1991 to 1997 from the British Household Panel Survey we investigate the incidence of housing finance problems, evictions and repossessions. Previous research on repossessions and problematic housing debt has focused on cross-sectional data. This paper contributes uniquely to the literature by examining the sequence of household and individual events associated with housing arrears and evictions. Our results show that previous experience of financial problems have a significant and positive association with the current financial situation, and that negative financial surprises are the main route into financial difficulties, controlling for other changes such as divorce or loss of employment. We also confirm the importance of structural, financial and personal factors in determining housing payment problems. Families with higher income, where the head or his/her spouse is in work, and those with greater assets have a lower risk of experiencing problems meeting their housing costs.
Keywords: 330